School of fear - Daneshvari, Gitty (Atom, 2012)
For the first time-maybe ever-Madeleine, Theo, Lulu, and Garrison are not looking forward to the start of summer, and three little words are to blame: School of Fear. In what they're sure will be the longest and most terrifying six weeks of their lives, the foursome must face their phobias head-on as students of the exclusive and elusive school. There's no homework or exams. But if they don't conquer their fears by the end of the summer, they'll find out just how frightening failing can be
Keywords: Fear / Juvenile fiction; Kinderbuch